Audio Hiding in Color Image Using SLT Schemes - AL-qaisi , Asmaa abdul-Razzaq (Iraqi Journal of Science, 2022)
As usage of internet grows in different applications around the world, many techniques were developed to guard an important data against from illegal access and modification from unauthorized users by embedding this data into visual media called host media. Audio hiding in an image is a challenge because of the large size of the audio signal. Some previous methods have been presented to reduce the data of the audio signal before embedding it in the cover image, however, these methods was at the cost of reducing the quality of the audio signal. In this paper, a Slantlet transform (SLT) based method is applied to obtain better performance in terms of audio quality. In addition, the data hiding scheme in the cover color image has been implemented using SLT matrix method. The simulation results prove that the proposed algorithm produce better performance in terms of audio quality and execution time in comparison with the existing DWT based schemes. Also, the proposed data hiding scheme takes good visual quality results and high data hiding capacity.